Unmasking MASC: Bringing to Light the Unique Morphologic, Immunohistochemical and Genetic Features of the Newly Recognized Mammary Analogue Secretory Carcinoma of Salivary Glands - Bishop, Justin A. (Springer US, 2013)
Mammary analogue secretory carcinoma (MASC) is a recently described salivary gland neoplasm that is characterized by its striking morphologic and molecular similarities to secretory carcinoma of the breast. This review highlights the characteristic clinical, histologic, immunophenotypic, and molecular features of MASC, and draws attention to the differential diagnosis of this increasingly recognized tumor.